Demography and migrations in globalization (2018)
Humanity has been in a demographic transition since Homo sapiens moved 70 000 years ago from East Africa through the Arabian Peninsula to conquer the planet. Historically, human beings have migrated to improve their living conditions or for security reasons. Due to current technologies, the established international order, and ease of transportation, the number of migrants —which is small compared to the world population— will grow and be increasingly composed of qualified individuals and people from developed countries. This book draws attention to the unprecedented turn and vertigo that twenty-first century globalization has caused in the historical demographic transition. Population grows less rapidly and is getting older, so age structure is changing and, with it, the consumption habits that impact economies.